Investigation of the Neumann triangle for dodecane liquid lenses on water - David, Robert; Dobson, Stephanie M.; Tavassoli, Zahra; Cabezas, M. Guadalupe; Neumann, A. Wilhelm (Colloids and surfaces. A, Physicochemical and engineering aspects, 2009)
Liquid lenses of dodecane resting on a water surface are imaged and analyzed computationally. The equilibrium condition for the three-phase line is a vector balance of three interfacial tensions known as the Neumann triangle. Measurement of the interfacial tensions, and two angles, allows the relation to be verified. Despite use of purified dodecane and the highest accuracy methods currently available at the millimetre length scale, a discrepancy with the Neumann triangle is found. The results, as well as literature data, are not consistent with interpretation as a thermodynamic line tension or as a pseudo-line tension. Alternative possibilities are briefly discussed.